Respon rumput Meksiko (Euchlaena mexicana) terhadap pemberian kompos rumen pada tanah berpasir - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2017)
The aim of this research is to know the effect of rumen compost on growth and production of Mexican grass (Euchlaena mexicana) on sandy soil and to know the dosage of rumen compost that giving the best result to growth and production of Mexican grass on sandy soil. This research was designed using Completely Randomized Design with single treatment of various doses of rumen compost (R) with 4 replications : r0 = no rumen compost (control), r1 = 10 tons ha-1, r2 = 20 tons ha -1, r3 = 30 tons ha-1 and r4 = 40 tons ha-1. The results of this study showed that rumen compost gave effect to the height of mexican grass plants 6 week after planting and 8 week after planting and crop production. The dosage of 30 ton ha-1 rumen compost gave the best effect to Mexican grass production. Key words : Rumen compost, Mexican grass, response, growth, production.